Design of Close-Fit Liners for the Rehabilitation of Gravity Pipes - Kampbell, Norman E.; Simicevic, Jadranka (Manuals and Reports on Engineering Practice Ser., 2021)
"MOP 145 provides a comprehensive explanation of the design of flexible, close-fit linings for the renewal or rehabilitation of pipes designed for gravity flow such as sanitary sewers, culverts, and storm sewers"--